1988
DOI: 10.1046/j.1537-2995.1988.28488265265.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of blood group antigens and alloantibodies among Chinese in Taiwan

Abstract: Most blood group antigens among Chinese people are very homogeneous (e.g., D, 99.4%; K, 0%; Fya, 99.7%). The frequency of clinically significant alloantibodies detected by the authors' crossmatching was only 0.146 percent, suggesting that pretransfusion testing can be greatly simplified in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 2 publications
7
43
3
Order By: Relevance
“…The nonsecrctor Lc(a+b-) phenotype, contrary to our previous report [1], is ab sent (or very rare) among Chinese in Tai wan. The reason for this discrepancy is due to the variation in strength of the Lc1 ' antigen in the Le(a+b+) phenotype.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The nonsecrctor Lc(a+b-) phenotype, contrary to our previous report [1], is ab sent (or very rare) among Chinese in Tai wan. The reason for this discrepancy is due to the variation in strength of the Lc1 ' antigen in the Le(a+b+) phenotype.…”
Section: Discussioncontrasting
confidence: 99%
“…If there was no inhi bition in any of the dilutions of antisera or lectin when compared with the saline control tubes of each dilution, then it was concluded that no salivary substance was present. We also retested with the above goat anti-Lea and anti-l.e1 ' the RBCs from several Chinese donors that we had previously re ported [1] as Le(a-l-b-). This was because in that re port a microplate technique had been used in which the Ortho goat anti-Le1 ' had been diluted 1:3 (stan dardized to detect the Le1 ' antigen of Caucasian Lc (a -b + ) RBCs but not of oriental Lc(a+b+) RBCs) and it had been noticed that, although the majority of the RBCs of these apparently *Le(a+b-)' individ uals gave a streaming pattern characteristic of a negative reaction, a small amount of the RBCs stuck to the center of the microplate well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of significant red cell alloantibodies was 6% in this study, much higher than other reports of similar eth nic groups [12]. The difference may have something to do with sampling, since all our patients received multiple transfusions rather than routine antibody screening.…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings indicate that the frequency of the Lewis-negative trait, obtained by molecular analysis of the three FUT3 SNPs studied, was about 10.8% in the population sample studied, which is close to the serological phenotype frequencies previously described for Asiatic populations (Lin-Chu et al, 1988;Liu et al, 1996Liu et al, , 1999.…”
Section: Discussionsupporting
confidence: 88%